Expression of the Motive of Traveling in Uzbek and English Folklore - Khalilova Rukhsora Kirolbek kizi; Kadirova Nargiza Arifovna (International Journal on Integrated Education, 2022)
This article analyzes the use of the motive of travel in English and Uzbek folklore examples-fairy tales and its meaning.